(Liquid + liquid) equilibrium for systems composed of clove and allspice essential oil compounds and hydrous ethanol at T = 298.2 K. (April 2016) - Koshima, Cristina C.; Umeda, Thayla K.; Nakamoto, Karina T.; Venâncio, Larissa L.; Aracava, Keila K.; Rodrigues, Christianne E.C.
Highlights: A fraction enriched in oxyterpenes can be obtained via the deterpenation process. Liquid extraction with hydrous ethanol can be applied to essential oil deterpenation. Distribution coefficients of caryophyllene, methyl eugenol and eugenol were studied. Eugenol has the highest distribution coefficient compared to the data in the literature. Phase compositions were well described by the NRTL parameters. Abstract: In the deterpenation process of essential oils, a fraction enriched in oxyterpenes is obtained. When compared to terpenic hydrocarbons, this fraction is more stable and soluble in water, maintaining the characteristic flavor and fragrance of the crude oil. Solvent extraction is an interestingly popular technique that is proposed for the fractionation of essential oils (once it can be performed under atmospheric pressure and ambient temperature) and contributes to the maintenance of the sensory quality of essential oils. The use of hydrous ethanol as a solvent for the (liquid + liquid) extraction process has shown advantages when the components of interest are completely soluble in ethanol, and their partition can be adjusted based on the level of hydration of the solvent. In addition, for some purposes, the fractions obtained from the separation process can be used without removing the solvent. Therefore, the primary goal of this study was to investigate the (liquid + liquid) equilibrium at T  = (298.2 ± 0.1) K of model systems composed of (caryophyllene + eugenol + ethanol + water) ( i.e., a clove essential oil model system) and (caryophyllene + methyl eugenol + eugenol + ethanol + water) ( i.e., an allspice essential oil model system) to provide the information required for the proper design and optimization of the associated deterpenation processes. For both systems studied, it was noted that increased water content in the solvent decreases the extraction of the essential compounds and increases the selectivity of the solvent. Oxygenated compounds ( e.g., methyl eugenol and eugenol) showed greater affinity for the solvent when compared to the sesquiterpenic hydrocarbon ( e.g., caryophyllene). The experimental values were correlated using the NRTL thermodynamic model, which provided a satisfactory performance and low deviations in the phase composition descriptions with global deviations near 0.0050 (mass fraction).